ANALISIS STRATEGI MARKETING MIX TERHADAP PRODUK TEH BUTONG PADA PT PERKEBUNAN NUSANTARA IV UNIT TEH BAH BUTONG: Analisis Strategi Bauran Pemasaran Produk Teh Butong Pada PT Perkebunan Nusantara IV (Unit Teh Bah Butong) - Afrilia, Dilla; Nirmala Sari , Tika (Universitas Jambi, 2025)
The rapid evolution of the Indonesian beverage industry has compelled traditional agribusiness firms to diversify their operations from bulk commodity production to consumer-oriented retail markets. As competition intensifies, state-owned enterprises (BUMN) must adopt sophisticated marketing frameworks to successfully transition into the Business-to-Consumer (B2C) segment. Within this context, PT Perkebunan Nusantara IV (PTPN IV) has strategically leveraged its heritage in tea production to establish a presence in the competitive retail landscape. This study aims to discover the implementation of the 7P marketing mix strategy by PT Perkebunan Nusantara IV Unit Bah Butongwhich released a new product to enter the retail market in Indonesia. The product is a black tea with the brand name “Teh Butong”. The teaproduced is categorized as powdered tea and teabags with premium and regular quality. This study uses qualitative methods with data collection using interviews and observation techniques of PTPN IV employees that are responsible for the teh Butong product. The results of the studyshowed the importance of implementing the 7P marketing mix strategy as an effective way to obtain the consumers. This study also explained how PTPN IV's efforts in maximizing the marketing activities of its new tea products by utilizing the 7P marketing mix strategy as an effort to increase sales to achieve the targets of the company. The findings imply that the company’s marketing mix strategy is centered on building brand loyalty within the local market to sustain competitiveness. It is also imperative for management to perform regular assessments of these strategies to drive sales growth and broaden market reach.